The Urgency of Ensuring the Conceptual Unity of Management Activities of Civic Organizations and State - Tokar, Marian (Pressing Problems of Public Administration, 2019)
An attempt has been made to actualize the issues of ensuring the conceptual unity of management activity of public organizations and the state. Much attention was paid to the effective cooperation of public organizations with state authorities, local self-government bodies, united territorial communities and appropriate support within the content of the state policy of promoting the development of civic organizations in Ukraine. The author proposes a “mutual assistance” method, which aims at increasing the level of reciprocity, in which institutional unity would become a priority direction of state policy. The necessity of developing new optimization approaches to the process of governing the state-building processes and the involvement of wider layers of civil society towards it has been emphasized. Accordingly, attention is drawn to its main task – to improve the integral and continuous state policy of promoting the development of such important institutions of civil society as public organizations, which, according to their capacity and essential functionality, possess signi cant potential for managerial mobilization of the national community. It has been proved that the development of civic organizations in modern Ukraine should be carried out according to certain systemic-synergetic parameters that are far from being integrated into the complex expression of the general construct of civil society, and sometimes they are quite unclear, sporadic, as much as possible chaotic outlines in the context of the participant of the socio-political discourse on the main levers of state development. The periods when the state is in socio-political situations and requires the adoption of fast and effective management decisions are outlined. Public institutions, as related to the allocation of public authority from society, may not always be able to respond in a timely manner to state-building challenges, become hostages to internal or external circumstances, and respond inadequately to the threats of national security, etc.It was stressed that only when state institutions consider public organizations as equal partners in ful lling social orders of citizens and stimulate cooperation with them primarily in educational, patriotic, educational, cultural and recreation spheres, rapid changes in the institutional psychology of state-building carriers are possible.